164 Effects of year-round supplementation of sugarcane molasses/urea or range cubes on growth performance of Bos indicus-influenced beef cows and their offspring. (29th July 2019) - Palmer, Elizabeth; Vedovatto, Marcelo; Ranches, Juliana; Gouvêa, Vinícius; Miranda, Miguel; Arthington, John; Vendramini, João; Moriel, Philipe
Abstract: This study compared the effectiveness of liquid sugarcane molasses/urea or wheat middlings-based range cubes supplementation on performance of beef cow-calf pairs. On d 0, 82 mature pregnant Brangus cows were stratified by BW and BCS (433 ± 47 kg; BCS = 4.6 ± 0.77) and randomly allocated into 1 of 6 bahiagrass pastures (13–14 pairs and 9.3 ha/pasture). Treatments were assigned randomly to pastures (2 pastures/treatment) and consisted of cows offered: winter supplementation of molasses/urea from calving until end of breeding season (d 161 to 300; MOL-W), or year-round supplementation of liquid urea/molasses (MOL-Y) or range cubes (CUB-Y). Supplement amount offered to cows differed monthly among treatments, but all cows were limit-fed 272 kg/yr of the respective supplement DM and similar trace mineral supplementation (336 g/cow/wk). Cubes were formulated to be isocaloric and isonitrogenous compared with molasses/urea (75% TDN, 20% CP; DM basis). Weekly supplement amount was divided in half and offered every Monday and Thursday. Cow BCS: did not differ among treatments from d 0 to 74 (P ≥ 0.56); was greater at calving (d 161) for MOL-Y and CUB-Y vs. MOL-W cows (P ≤ 0.05); and was greatest, intermediate, and least at start of breeding season (d 217) for MOL-Y, CUB-Y, and MOL-W cows (P ≤ 0.05), respectively. Liver concentrations for Co, Se, and Cu on d 122 and 217 were greater (P ≤ 0.02) for CUB-Y vs. MOL-W and MOL-Y cows. Calving date, percentage of pregnant cows on d 360, and calf birth BW, pre-weaning ADG, and BW at weaning did not differ (P ≥ 0.14) among treatments. Therefore, year-round supplementation of liquid molasses/urea and range cubes enhanced cow BCS at calving and start of breeding season but did not impact subsequent reproductive performance of cows and calf weaning weights than conventional winter molasses/urea supplementation of cows